Application of Transfer Learning Technique for Detection and Classification of Lung Cancer using CT Images (International Journal of Scientific Research and Management (IJSRM), 2021)
Lung cancer is unquestionably a lung-influencing chronic condition that significantly hampers the respiratory system. It is the second most dangerous disease which causes increase in death rate. To resolve this issue, we had planned to create a very Convolutional Neural Network using Transfer learning to specifically classify the lungs CT scans as normal, malignant, or benign in a subtle way. A dataset of 1100 lung CT scans is used for this purpose. For the most part, five Transfer Learning architectures are compared extensively in this classification such as MobileNet, VGG16, VGG19, DenseNet-201 and ResNet-101. Out of which, DenseNet-201 performed the best. The proposed strategy achieved a mean accuracy of 53 percent in the trials and 43% of mean F1-score, mean precision and mean recall.